2004
DOI: 10.1520/cca11911
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature-Match-Curing on Freeze-Thaw and Scaling Resistance of High-Strength Concrete

Abstract: As a part of a comprehensive study to evaluate the effects of elevated curing temperatures on hardened concrete properties, four non-air-entrained high-strength concrete (HSC) mixtures were prepared at temperatures ranging from 10 to 35°C. After mixing, 5.5 liters of concrete were placed inside a large polystyrene block to simulate temperature development in HSC structural members. The concrete temperature inside the block was continuously monitored with thermocouples, and collected temperature information was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…This procedure has been found to be detrimental to the scaling resistance of the concrete. However, some authors 16–18 have found an improvement of the scaling resistance of the high‐strength concrete when passing from 20 to 60 °C at early ages of the concrete.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure has been found to be detrimental to the scaling resistance of the concrete. However, some authors 16–18 have found an improvement of the scaling resistance of the high‐strength concrete when passing from 20 to 60 °C at early ages of the concrete.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] This procedure has been found to be detrimental to the scaling resistance of the concrete. However, some authors [16][17][18] have found an improvement of the scaling resistance of the high-strength concrete when passing from 20 to 60 • C at early ages of the concrete. The objective of this paper is to study the influence of the curing conditions of the concrete when it is cast under summer conditions (high temperature and low humidity) in the internal deterioration and scaling resistance under freeze-thaw cycles (winter conditions).…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al carry out a test of a pre-stressed concrete (PC) beam for hardening process monitoring purpose using fiber Bragg grating (FBG) sensors [2]. Jonsson and Olek used thermocouples to continuously monitor the curing temperature of the concrete, and evaluated the effects of elevated curing temperatures on hardened concrete properties [3]. Saafi and Romine developed a new technique to monitor concrete setting and hardening, which consisted of embedding MicroElectro-Mechanical System (MEMS) devices into concrete during construction [4].…”
Section: Introductionmentioning
confidence: 99%
“…The properties of ultrasonic vibration or wave propagation, such as velocity or attenuation, are affected by the change of physical properties. Thus, the strength development can be monitored, by tracking the change of ultrasonic signals (Gu et al 2006;Jonsson and Olek 2004;Oh et al 2016;Shin et al 2008;Kim et al 2013Kim et al , 2015Tawie et al 2010). Furthermore, a range of methods based on the acoustical, electrical, magnetic, optical, radiographic, and other mechanical properties of concrete have been studied (ACI Committee 228 2003;Lamond and Pielert 2006).…”
Section: Introductionmentioning
confidence: 99%